2018
DOI: 10.5815/ijisa.2018.05.06
|View full text |Cite
|
Sign up to set email alerts
|

Passenger Body Vibration Control in Active Quarter Car Model using Hybrid ANFIS PID Controller

Abstract: Abstract-The objective of this paper is to improve the passenger ride comfort and safety in an active quarter car model. For this purpose, a quarter car model with passenger body and seat is considered to capture the dynamic behaviour of a real complete car system. To achieve the desired target, two different controllers such as Adaptive Neuro Fuzzy (ANFIS) controller and Hybrid ANFIS PID controller (HANFISPID) are designed. The controllers selection and design was aimed to achieve good passenger ride comfort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…[4] and [5] have investigated the use of PID controllers in active suspension systems, highlighting the role of intelligent controllers such as adaptive neural networks and fuzzy logic in enhancing passenger comfort. Additionally, the study by [6] demonstrated the improved performance of PID controllers in active quarter-car models, specifically addressing passenger ride comfort and vehicle handling issues.…”
Section: Introductionmentioning
confidence: 98%
“…[4] and [5] have investigated the use of PID controllers in active suspension systems, highlighting the role of intelligent controllers such as adaptive neural networks and fuzzy logic in enhancing passenger comfort. Additionally, the study by [6] demonstrated the improved performance of PID controllers in active quarter-car models, specifically addressing passenger ride comfort and vehicle handling issues.…”
Section: Introductionmentioning
confidence: 98%
“…Simulations show the effectiveness of the NN compared to all these systems. A quarter car model with passenger body and seat was developed by [9] to capture the dynamic behavior of a car to improve ride comfort and safety. Two controllers, which are Adaptive Neuro-Fuzzy Inference System (ANFIS) and Hybrid ANFIS PID (HANFISPID) was developed by [9].…”
Section: Introductionmentioning
confidence: 99%
“…A quarter car model with passenger body and seat was developed by [9] to capture the dynamic behavior of a car to improve ride comfort and safety. Two controllers, which are Adaptive Neuro-Fuzzy Inference System (ANFIS) and Hybrid ANFIS PID (HANFISPID) was developed by [9]. Results demonstrate that the proposed HANFISPID control plan achieves better ride comfort and safety of travel compared to the passive system and ANFIS controller.…”
Section: Introductionmentioning
confidence: 99%